PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PENGGELAPAN TERHADAP KENDARAAN RODA EMPAT DENGAN MODUS SEWA RENTAL (STUDI PUTUSAN NO 69/PID.B/2020/PN.BBU) - Gunawan, Dheri; Rusli, Tami (IBLAM LAW REVIEW, 2021)
The convenience provided by rental car owners is often abused by irresponsibletenants, car damage due to improper use, used as a means of committing crimeseven to embezzlement of the car by way of selling or being pawned is a risk thatcan befall the car owner at any time. rental. As was the case with Effendi BinBunyamin, a resident of Palm Raya village, Indralaya Subdistrict, Ogan IlirRegency, South Sumatra Province, who committed embezzlement of a fourwheeled vehicle belonging to Muhammad Sholeh using rental rental mode. Theresearch method used in this thesis research is a normative juridical approachand an empirical approach. Data collection based on library research and fieldstudies. Resource persons in this study include investigators, public prosecutors,and judges. The factor that caused the defendant to embezzle four-wheeledvehicles was due to economic factors. Where the defendant needed an amount ofmoney to be used for the cost of marrying his child so that this situation forced thevictim to commit the crime of embezzlement as in decision no 69 / Pid.B / 2020 /Pn.Bbu. Criminal responsibility for the defendant, namely that the defendant wassecured by members of the Way Kanan resort police, was then detained duringthe investigation and trial process and then sentenced to prison for one year andfive months as stated in decision number 69 / Pid.B / 2020 / Pn.Bbu.Keywords: judge consideration, embezzlement, mode, rental.